2020
DOI: 10.1007/s00262-020-02484-0
|View full text |Cite
|
Sign up to set email alerts
|

New targets for therapy: antigen identification in adults with B-cell acute lymphoblastic leukaemia

Abstract: Acute lymphoblastic leukaemia (ALL) in adults is a rare and difficult-to-treat cancer that is characterised by excess lymphoblasts in the bone marrow. Although many patients achieve remission with chemotherapy, relapse rates are high and the associated impact on survival devastating. Most patients receive chemotherapy and for those whose overall fitness supports it, the most effective treatment to date is allogeneic stem cell transplant that can improve overall survival rates in part due to a 'graft-versus-leu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…BTK has been found abnormally expressed in ALL [ 148 , 149 ] and pre-B cells have shown high sensitivity to ibrutinib in preclinical models of B-ALL [148] . Other example is survivin, an apoptosis inhibitor and cell cycle regulator that is expressed in many types of tumors (including ALL) and is associated with chemoresistance [ 150 , 151 ]. Several clinical trials have found survivin as a therapeutic target to ALL [152] , [153] , [154] .…”
Section: Other Pharmacogenes As Future Possibilities In the Field Of mentioning
confidence: 99%
“…BTK has been found abnormally expressed in ALL [ 148 , 149 ] and pre-B cells have shown high sensitivity to ibrutinib in preclinical models of B-ALL [148] . Other example is survivin, an apoptosis inhibitor and cell cycle regulator that is expressed in many types of tumors (including ALL) and is associated with chemoresistance [ 150 , 151 ]. Several clinical trials have found survivin as a therapeutic target to ALL [152] , [153] , [154] .…”
Section: Other Pharmacogenes As Future Possibilities In the Field Of mentioning
confidence: 99%
“…Despite the significant improvement in pediatric patients' outcomes, B-ALL represents a devastating, poor-prognosis disease in adults as only 30-40% of those patients achieve long-term remission (Terwilliger and Abdul-Hay, 2017;Jordaens et al, 2020). In the era of personalized medicine, it may be important to identify explicit prognostic parameters that allow better patients' stratification aiming to provide the optimum therapeutic regimen for each particular case.…”
Section: Isolated Myeloperoxidase Immunohistochemical Expression In Bone Marrow Biopsy Depicts Clinical Outcomes In Adults With Typical Bmentioning
confidence: 99%